Estudos sobre o envolvimento de “membrane rafts” e a ativação de quinases de células epiteliais durante a interação com paracoccidioides brasiliensis - Maza, Paloma Korehisa [UNIFESP] (2008)
Many pathogens are able to manipulate host cell signaling in order to facilitate infection. In this thesis, we demonstrated that the fungus Paracoccidioides brasiliensis promotes an increase of ERK12 and SFK activation in A549 epithelial cells (human lung cells), by approximately 6- and 7-fold over basal levels, respectively. By using PP2, inhibitor for SFK activity, and PD98059, inhibitor for ERK1/2 activation, we verified that ERK1/2 activation is partially dependent of activated SFKs and probably other kinases are involved in this event. Besides modulation of host cell signaling, several studies have been demonstrated that pathogens hijack domains that are present in host cell membranes called membrane rafts, which are cholesterol- and sphingolipidenriched domains, that are involved in several cell events, including cell signaling. By using several approaches, such as membrane rafts disruption with cholesterolextractor (methyl-β-cyclodextrin, MβCD) or –binding (nystatin) drugs, and the localization of ganglioside GM1, a membrane raft marker, by using cholera toxin subunit B (CTB), we showed the involvement of these epithelial cell membrane domains in P. brasiliensis adhesion. By isolating detergent-resistant membrane (DRM) from epithelial cells after incubation with this fungus, we showed the activation and the dislodgment of SFKs to fractions which contain membrane rafts. Moreover, we verified that cholesteroldepletion with MβCD completely inhibits SFK activation, corroborating the importance of membrane domains in activation of these kinases.The results presented in this thesis demonstrate for the first time that pathogenic fungi may modulate the organization and activity of host cell membrane rafts for infection establishment.